MULTI-CRITERIA ANALYSIS OF UAVS REGULATIONS IN 6 COUNTRIES USING THE ANALYTICAL HIERARCHICAL PROCESS AND EXPERT KNOWLEDGE - A. C. Morales; D. Paez; C. Arango (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
To analyze the current situation of Colombian regulation, it is necessary to compare some specific aspects with the legislation used in other countries where the UAVs topic dates to many years ago. This study is focused on evaluating all the possibilities to make the Colombian regulation effective without closing opportunities of research and development growth, but still guarantee the privacy and intimacy rights of the population. Results from our study are currently being used in the development of the Colombian regulation and they are proven useful to instigate informative debates and identify areas where specific needs are to be address in Colombia.